Early Pro-inflammatory Microglia Activation After Inflammation-Sensitized Hypoxic-Ischemic Brain Injury in Neonatal Rats - Serdar, Meray; Kempe, Karina; Rizazad, Mandana; Herz, Josephine; Bendix, Ivo; Felderhoff-Müser, Ursula; Sabir, Hemmen (Frontiers in Cellular Neuroscience, 2019)
Background: Perinatal asphyxia, leading to neonatal encephalopathy, is one of the leading causes for child mortality and long-term morbidities. Neonatal encephalopathy rates are significantly increased in newborns with perinatal infection. Therapeutic hypothermia is only neuroprotective in 50% of cooled asphyxiated newborns. As shown experimentally, cooling has failed to be neuroprotective after inflammation-sensitized hypoxic ischemic (HI) brain injury. Microglia are thought to be key players after inflammation-sensitized HI brain injury. We performed this study investigating early microglia phenotype polarization in our newborn animal model of inflammation-sensitized HI brain injury, better understanding the underlying pathophysiological processes. Methods: Seven day old Wistar rat pups were injected with either vehicle (NaCl 0.9%) or E. coli lipopolysaccharide (LPS), followed by left carotid ligation combined with global hypoxia inducing a mild unilateral hypoxic-ischemic injury. Pups were randomized to (1) Sham group (n=41), (2) LPS only group (n=37), (3) Veh/HI group (n=56) and (4) LPS/HI group (n=79). On postnatal day 8 and 14 gene-expression analysis or immunohistochemistry was performed describing early microglia polarization in our model. Results: We confirmed that LPS pre-sensitization significantly increases brain area loss and induced microglia activation and neuronal injury after mild hypoxia-ischemia. Additionally, we show that microglia upregulate pro-inflammatory genes involving NLRP-3 inflammasome gene expression 24 h after inflammation-sensitized hypoxic-ischemic brain injury. Conclusion: These results demonstrate that microglia are early key mediators of the inflammatory response following inflammation-sensitized HI brain injury and that they polarize into a predominant pro-inflammatory phenotype 24 h post HI. This may lead to new treatment options altering microglia phenotype polarization early after HI brain injury.